RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU YAYASAN JAYA MANGGALA SCHOOL BERBASIS WEB - Salomo Lumban Tobing, Ruben Alpha; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2021)
Dhamma Sasana School is a school under the auspices of the Jaya Manggala foundation which was established in 2017, which has a problem in the registration process, namely the registration process does not have a website and still uses the old and manual registration procedure. The aim of this research is to transform the old and manual registration system into an effective website, can be accessed anywhere, easily gets instant information and verifies student data accurately, quickly and safely. The research method used is the Waterfall method. This method is an ordered method to develop existing systems on the website. This research resulted in the registration process for prospective students and the verification process going online. The system for building websites is by using the programming language PHP5, Javascript, MySQL Database, Notepad ++ Text Editor and the Bootstrap Framework. The conclusion from the researchers is that with the existence of a website, schools can streamline school expenditure, making it easier for parents to register their children only through the internet and the committee both in storing and verifying prospective student data.